Physiologie der Kopfhaut - Rukwied, Roman (Der Hautarzt, 2017)
Background: Human scalp reveals a remarkable difference to hairy skin of other body regions. The structure of the scalp offers effective protection against water loss and contributes to thermoregulation due to significant vascularization. The scalp is innervated by the trigeminus nerve.Objectives: The majority of the population complain about “sensitive” scalp. However, sensory, regional, ethnic or pathologic parameters contributing to “sensitive” scalp are largely unknown.Materials and methods: Quantitative sensory tests and superficial topical application test of irritant substances were performed.ResultsExtremely high thresholds to thermal and mechanical stimuli were recorded at the vertex compared to occipital or temporal scalp regions, or the hairy skin of other body regions such as trunk or distal extremities. Pronounced scalp hypersensitivity can be found in Asians as compared to Caucasians and under pathologic conditions, such as alopecia, dandruff, or migraine.Conclusions: Putative causes of “sensitive” scalp can be a facilitated transdermal penetration of irritant substances, altered neuronal innervation or receptor expression, or peripheral and central sensitization of sensory afferents.